Dungeons & dragons player's handbook - Crawford, Jeremy; Perkins, Christopher, 1968-; Petrisor, Ben; Schneider, F. Wesley; Winninger, Ray; Wyatt, James, 1968-; De Armas, Makenzie (Wizards of the Coast LLC, 2024)
"This revised and expanded Player's Handbook® is the essential reference for every fifth edition Dungeons & Dragons player. It contains rules for character creation and advancement, exploration, combat, equipment, spells, and much more. Create fantastic D&D® heroes from the wide selection of character origins, classes, and subclasses provided. Explore ancient ruins and deadly dungeons. Battle monsters while searching for legendary treasures. Gain experience and power as you trek across uncharted lands with your companions."--Back cover.